Aktivitas Antioksidan pada Formulasi Minuman Serbuk Instan dari Sari Daun Suruhan (Peperomia pellucida): Antioxidant Activity in Instant Powder Drink Formulation from Suruhan Leaf Extract (Peperomia pellucida) - Meilina Purnama Ningrum; Juniza Firdha Suparningtyas; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Suruhan leaves empirically been used as medicine, because has an antioxidant activity that can counteract free radicals that cause various diseases. This study aimed to determine the antioxidant activity of instant powder drinks. This research method was carried out by filtering extract, test the characteristics and antioxidant activity of extracts, formulation and evaluation of instant powder drink used the foam mat drying method, and test the antioxidant activity of the preparations used the 1,1-Diphenyl-2picryl Hydrazyl (DPPH) method. The results showed that the extract of Suruhan Leaf contained alkaloids, flavonoids, terpenoids, saponins, and polyphenols. The extract has a very strong IC50 of 8.8 ppm. The research used the 20% concentration of extract to be formulated as the instant powder drink. The results of the evaluation of physical properties showed that the formulation has green color, in powder form, odorless, pH 5,84, humidity 6,84%, ash content 0,49%, flow rate 3,98 g/s, angle of repose 25,22?, compressibility 26,07%, and dissolving time 68 seconds. Only some of the physical properties of powder have met the requirements of a good powder. IC50 of instant powdered drink preparation is 387,265 ppm, indicating that the preparations antioxidant activity is in the very weak category.